768 The Device for Intraventricular Entry (DIVE) Guide: A Novel Solution to a Perpetual Problem. (April 2023) - Blue, Rachel; Jabarkheel, Rashad; Ajmera, Sonia; Tomlinson, Samuel; Miranda, Stephen; Schuster, James M.; Spadola, Michael
Abstract : INTRODUCTION: Safe and reliable access to the ventricular system is a necessary skill in the neurosurgical armamentarium. The freehand technique for catheter placement remains an accepted method, yet the inaccuracy rate can be as high as 40%, with as many as 3 passes per procedure, and complication rates between 10-40%. A number of devices have been developed to assist with catheter placement, however, these devices inhibit ergonomics or require larger incisions and expensive navigation technology. METHODS: A novel device for ventricular entry, the DIVE guide, was designed by the first and senior author. 50 patients undergoing extra ventricular drain (EVD) or shunt placement were prospectively enrolled for DIVE assisted catheter placement under an IRB approved study with a non-significant risk (NSR) device designation. The primary outcome is catheter location on CT. Secondary outcomes include number of catheter passes, clinically significant hemorrhages and procedure-related infections. RESULTS: 50 patients were enrolled at a single academic center for ventricular access with DIVE assistance. Indications included subarachnoid or intraventricular hemorrhage, TBI, hydrocephalus, pseudotumor and post-surgical wound drainage. 76% (38/50) underwent right sided placement and 24% (12/20) underwent left. 100% (50/50) had successful cannulation in an average of 1.06 passes. Post procedure head CT confirmed ipsilateral frontal horn or 3rd ventricle placement (Kakarla Grade 1) in 92% (46/50) and 8% (4/50) in the contralateral lateral ventricle (Grade 2). There were no significant tract hemorrhages or procedural infections. CONCLUSIONS: This a prospective study to investigate the safety and efficacy of DIVE-assisted ventricular access. 100% of procedures had successful ventricular cannulation, with 92% achieving Kakarla Grade 1, in an average of 1.06 passes.